(untitled) (Itinera, 2025)
This paper investigates the relationship between immersion, emotion, and imagination in virtual reality (VR), focusing on two seemingly distant domains: Alejandro G. Iñárritu’s installation Carne y Arena (2017) and VR-based workplace safety training. Both cases demonstrate that simulated environments can elicit authentic emotional responses – such as fear, stress, or vulnerability – yet the implications of these experiences diverge sharply. Drawing on theories of presence and the “paradox of fiction”, we argue that VR should be understood not as a substitute for imagination but as a heightened form of fiction that depends on the user’s willingness to engage in make-believe. While Carne y Arena frames affect as an entry point for moral imagination within an explicit artistic and symbolic context, occupational safety training instrumentalizes emotion as a means of behavioral conditioning within a productivist framework. The danger in both domains lies not in immersive experience itself but in mistaking a single simulation for the fullness of lived reality.